Meeting the Public Health Workforce's Training Priorities in Georgia and the Southeast - Laura Lloyd; Melissa Alperin; Michelle Carvalho; Kathleen Miner (Georgia Southern University, 2016)
Background: The mission of the Region IV Public Health Training Center (R-IV PHTC) is to build knowledge and skills in the public health workforce in the eight states of HHS Region IV by providing competency-based training. Workforce training needs are changing quickly and dramatically in light of new developments in public health practice and science, emerging diseases, changes in the health care environment, and the growing emphasis on inter-professional practice. Additionally, a 2014 survey conducted by the Association of State and Territorial Health Officials (ASTHO) found that at least 38% of the current public health workforce plans to retire by 2020. Therefore, it is increasingly crucial to prepare upcoming managers for leadership positions and to train entry-level workers to assume more advanced roles. Methods: To address current and emerging training needs in Georgia and the southeast, the R-IV PHTC continually identifies emerging priorities and effective training approaches. It explores training needs through a review of formal needs assessments, key stakeholder interviews, surveys of targeted audiences, informal partner communications, and training evaluation data. An interactive component of the GPHA session allowed participants to identify and discuss their own professional training needs. Results: Workforce development needs assessments data across several southeastern states identified recurring training needs for professionals in Tiers 1, 2 and 3 of the Council on Linkages Core Competency domains for Analytical/Assessment Skills and Financial Planning/Management. In Georgia, top competency training needs gathered from a variety of assessment methods included Cultural Competency, Communication, Financial Planning/Management, Public Health Science, and Leadership/Systems Thinking. Participants in the workshop's interactive component expressed highest personal need for training in Financial Planning/Management, Analytical/Assessment Skills, and Policy Development/Program Planning. However, for others in their organizations, they identified a priority need for leadership training. Conclusions: The R-IV PHTC assesses training needs and provides training resources to respond to current and emerging public health workforce development needs in Georgia and the southeast.